2010
DOI: 10.1212/wnl.0b013e3181e396ea
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of cerebral microbleeds

Abstract: In addition to APOE genotype, presence and progression of small-vessel disease and vascular risk factors were predictors of new MBs. The latter are potentially modifiable, suggesting the possibility of preventing incident MBs, hopefully resulting in slower clinical decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
2
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(81 citation statements)
references
References 37 publications
7
66
2
6
Order By: Relevance
“…9,10 However, only 1 study made separate categories according to CMB location and they did not find a relation of vascular risk factors and incidence of deep or infratentorial CMBs. 9 In our study, the association between vascular risk factors and incident deep or infratentorial microbleeds remained significant after adjustment for other markers of small vessel disease. This suggests that deep or infratentorial microbleeds are an independent indicator of hypertensive vasculopathy.…”
Section: Poels Et Al Incidence Of Cerebral Microbleeds 659mentioning
confidence: 98%
See 1 more Smart Citation
“…9,10 However, only 1 study made separate categories according to CMB location and they did not find a relation of vascular risk factors and incidence of deep or infratentorial CMBs. 9 In our study, the association between vascular risk factors and incident deep or infratentorial microbleeds remained significant after adjustment for other markers of small vessel disease. This suggests that deep or infratentorial microbleeds are an independent indicator of hypertensive vasculopathy.…”
Section: Poels Et Al Incidence Of Cerebral Microbleeds 659mentioning
confidence: 98%
“…In contrast to the baseline cross-sectional study, 5 we now also found an association between white matter lesion volume at baseline and incidence of strictly lobar microbleeds, which is in line with other studies. 9,11 It may be hypothesized that vascular amyloid deposition alters white matter perfusion and thus causes white matter lesions through vessel stenosis, vasoactive effects of ␤-amyloid, and smooth muscle cell necrosis that results in loss of vasoreactivity. 19,20 In our study, in 12 persons (1.4% of overall study population; 5.9% of persons with CMBs at baseline), some CMBs that were present at baseline seemed to disappear over time.…”
Section: Poels Et Al Incidence Of Cerebral Microbleeds 659mentioning
confidence: 99%
“…28,29 By its restriction to fully published studies, our systematic review is potentially subject to publication bias. 30 Furthermore, although we sought some additional unpublished data, only 4 studies in around two-thirds of the total number of participants from relevant studies contributed data on the association Figure 3 Meta-analysis of the association between ⑀2؉ vs ⑀3/3 genotypes and brain microbleeds (BMBs) (A) BMBs in any location.…”
Section: Resultsmentioning
confidence: 99%
“…CMBs are frequently identified in patients followed in memory clinics (Cordonnier et al., 2006; Goos et al., 2010). In line with previous studies, we identified a greater age and hypertension as risk factors associated with CMBs.…”
Section: Discussionmentioning
confidence: 99%